Matéria seca, cálcio e fósforo em rações para ovinos, contendo farelo de algodão, levedura e uréia - Sampaio, Alexandre Amstalden Moraes [UNESP]; Ezequiel, Jane Maria Bertocco [UNESP]; De Oliveira, Mauro Dal Secco [UNESP]; De Figueiredo Vieira, Paulo [UNESP] (My University, 1996)
This experiment was carried out with 24 male lambs of Polwarth (Ideal) breed with 21 kg of mean live weight. Digestibility of isoproteic rations including three different protein sources (cottonseed meal, RA; dry yeast, RL; and urea, RU) was studied. Data were analized in a completely randomized design with three treatments and eight replications. Digestibility coefficients of dry matter were smaller (P<0.05) in ration RA (58.29%) than in rations RU and RL (64.07 and 62.19%). The mean amounts of apparent absorption of mineral matter did not change significatively (P>0.05) among rations. The mean quantities of calcium and phosphorus absorbed did not differ (P>0.05) among treatments, with values of 26.53; 30.04 and 34.97% for calcium and 24.67; 43.10 and 32.40% for phosphorus in rations RA; RL and RU, respectively. Based on these results, and considering the data examined, it was concluded that the use of these three sources of protein can be employed for growing lambs.

O experimento foi conduzido utilizando-se de 24 borregos Ideal com peso médio de 21 kg. Estudou-se a digestibilidade aparente da matéria seca, proveniente de rações isoprotéicas e isocaléricas constituídas por três diferentes fontes protéicas: RA= ração com farelo de algodão; RL= ração com levedura e RU= ração com urdia. Também avaliou-se a absorção aparente da matéria mineral, do cálcio e do fósforo. O delineamento utilizado foi o inteiramente casualizado, com três tratamentos e oito repetições. Os coeficientes de digestibilidade aparente da matéria seca diferiram significativamente (P < 0,05), com superioridade das rações RU e RL (64,07 e 62,19%) em relação à ração RA (58,29%). As quantidades médias de absorção aparente da matéria mineral, não variaram significativamente (P > 0,05) nas rações experimentais. As quantidades médias de cálcio e fósforo absorvidos não diferiram (P > 0,05) em relação aos tratamentos estudados, com valores de 26,53; 30,04 e 34,97% do cálcio e 24,67; 43, 10 e 32,40% do fósforo das rações RA, RL e RU, respectivamente. Estes resultados indicaram que as diferentes fontes protéicas estudadas podem ser utilizadas para o crescimento de ovinos no que diz respeito A utilização da matéria seca, cálcio e fósforo.
Dry matter, calcium and phosphorus in ovine rations containing cottonseed meal, yeast and urea
Keywords: Dry yeast; Isocaloric; Male lambs; Polwarth breed; Proteic sources